How Does The Ability of Pedagogical Content Knowledge Preservice Teacher Students in Mathematics Learning? - Dedi Muhtadi; YL Sukestiyarno; Isti Hidayah; Amin Suyitno (International Conference on Science, Education, and Technology, 2022)
Abstract. The purpose of this study was to determine how the ability of Pedagogical Content Knowledge (PCK) of prospective teacher students in learning mathematics. The research method uses a qualitative approach with case studies. The data analyzed came from three groups of prospective mathematics teacher students with very good, good, and sufficient levels through concept understanding tests, vignettes, and interviews. The results showed that students with excellent and good academic abilities had relatively the same content, teaching, and student knowledge. Content knowledge is at level 1, teaching knowledge is at level 2, and knowledge about students is at level 1. At the same time, students with sufficient academic ability are at level 0 for content knowledge.